Two new species of Cladoceran crustaceans of the genera macrothrix baird and Alona baird from Malaysia - Idris, B. A. G.; Fernando, C. H. (Springer-Verlag, 1981)
Two new species of Cladocera were found -during an intensive study of Malaysian zooplankton. Macrothrix malaysiensis sp, nov. is unique in the genus in 'possessing a characteristic posterodorsal spine on the carapace. The structure of the antennules is also diagnostic. Alonafreyi sp. nov. closely resembles A. verrucosa Sars and A. rigidicaudis (Smirnov). However, it can be diagnosed by the characteristic head shield, labral plate, ventral setae and the structure of the postabdomen.